1992
DOI: 10.1071/ar9920203
|View full text |Cite
|
Sign up to set email alerts
|

Response of annual medics (Medicago spp.) and field peas (Pisum sativum) to high concentration of boron: genetic variation and the mechanism of tolerance

Abstract: The genetic range and mechanism of tolerance to high concentrations of B were examined for field peas and annual medic species. Both genera showed a wide range in response to B. The most tolerant Australian varieties of pea included Early Dun, Partridge, Dun, Derrimut, Dundale, Alma and Maitland, while Parraggio, Ghor and Cyprus were the most tolerant of the Australian medics. Accessions more tolerant than the Australian varieties were identified for both species. The highest percentage of tolerant accessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 8 publications
1
35
0
Order By: Relevance
“…Genetic variation in response to boron has been reported for wheat and barley (Moody et al ., 1988 ;Nable, 1988 ;Paull et al ., 1988, Nable et al ., 1990 and medics and peas (Bagheri et al ., 1992 ;Paull et al ., 1992) . Tolerant lines of all these species maintain relatively low concentrations of boron in roots and shoots (Nable, 1988 ;Paull et al ., 1992) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variation in response to boron has been reported for wheat and barley (Moody et al ., 1988 ;Nable, 1988 ;Paull et al ., 1988, Nable et al ., 1990 and medics and peas (Bagheri et al ., 1992 ;Paull et al ., 1992) . Tolerant lines of all these species maintain relatively low concentrations of boron in roots and shoots (Nable, 1988 ;Paull et al ., 1992) .…”
Section: Introductionmentioning
confidence: 99%
“…A limited range in genetic variation in boron tolerance was identified among Australian pea varieties (Bagheri et al ., 1992 ;Paull et al ., 1992) and preliminary investigations indicated that the variation in response to boron among a collection of Pisum sativum was greater than that in Australian commercial varieties (Materne, 1989 ;Paul] et al ., 1992) . The first major objective of the work reported here was to survey a large number of accessions to gain a comprehensive summary of the extent and geographical distribution of boron sensitivity and tolerance in Pisum sativum and to identify sources of tolerance for the breeding program .…”
Section: Introductionmentioning
confidence: 99%
“…However, according to the previous studies, they are mainly associated with B exclusion from roots, reduced translocation to shoots and avoidance by means of shallow root systems. The ability to restrict B uptake into the plants can minimize the physiological impairments caused by B toxicity (Nable, 1988;Nable et al, 1997;Paull et al, 1992;Hayes and Reid, 2004). On the other hand, an inherent ability to tolerate excessive B concentration in plant tissues (Torun et al, 2006) or the differential antioxidant response that may reduce B-toxicity damage in some species (Cervilla et al, 2007) was suggested.…”
Section: Introductionmentioning
confidence: 99%
“…The dominance of tolerant varieties in specific regions indicates that high concentrations of B exert a significant selection pressure and influence the distribution of wheat varieties. Further evidence of the influence of B on agriculture in southern Australia is derived from the fact that the pea variety Early Dun, introduced to Australia during the 19th century, is not only among the most tolerant of Australian pea varieties (Paull et al, 1992), but is also still one of the most widely grown.…”
Section: Boron Tolerance Of Wheat 253mentioning
confidence: 99%
“…and peas (Pisum sativum) (Paull et al, 1992) have identified an apparently similar mechanism controlling tolerance to B for these species. The low concentrations of B in roots indicate that the low concentrations measured in shoots Of tolerant lines result from the lower uptake of B by tolerant lines rather than restricted translocation of B from roots to shoots.…”
Section: Physiological Control Of B Tolerancementioning
confidence: 99%